Assessment of residual stress distribution of sequential welding and machining process by consecutive finite element analysis - (:unkn) unknown (International Conference on Fracture, 2017)
A Finite Element Analysis (FEA) Modeling has been investigated to predict the effect of residual stresses which was caused by first welding and then machining process. A consecutive FEA model which has enabled to consider the internal stresses of welding while simulating machining has been developed to increase the efficiency of the numerical simulations. MSC.Marc Mentat software was used as computational tools to generate the 3-D mesh and model the welding and machining process under non-linear simulation conditions. Cutting paths are predetermined via a CAM software and integrated into the numerical model as a CCL file. The results of the consecutive simulations were revealed that the proposed model provides better results if compared to nonconsecutive simulation. © 2017 Chinese Society of Theoretical and Applied Mechanics. All Rights Reserved.